2023
DOI: 10.1177/10105395231158868
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Low Birth Weight in the Solomon Islands: Evidence From the 2015 Solomon Islands Demographic and Health Survey data

Abstract: Low birth weight (LBW) has contributed to more than 80% of under-5 deaths worldwide, most occurring in low- and middle-income countries. We used the 2015 Solomon Islands Demographic and Health Survey data to identify the prevalence and risks associated with LBW in the Solomon Islands. Low birth weight prevalence estimated was 10%. After adjustment for potential confounders, we found the risk of LBW for women with a history of marijuana and kava use was 2.6 times, adjusted relative risk (aRR) 2.64 at a 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Beyond the prenatal period, pre-conception exposure may predispose offspring to later-life obesity and cardiometabolic disease, but the evidence is inconsistent. Two human epidemiologic studies reported that pre-conception exposure to cannabis was associated with lower birth weight [ 99 , 100 ]. This may occur through the disruption of oocyte maturation [ 101 ] or through epigenetic changes to sperm among paternal cannabis users [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the prenatal period, pre-conception exposure may predispose offspring to later-life obesity and cardiometabolic disease, but the evidence is inconsistent. Two human epidemiologic studies reported that pre-conception exposure to cannabis was associated with lower birth weight [ 99 , 100 ]. This may occur through the disruption of oocyte maturation [ 101 ] or through epigenetic changes to sperm among paternal cannabis users [ 102 ].…”
Section: Discussionmentioning
confidence: 99%